2013
DOI: 10.1111/inr.12015
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based distance learning for nurse education: a systematic review

Abstract: Web-based education has encouraging effects in improving both participants' knowledge and skills performance, and in enhancing self-efficacy in performing nursing skills, with a high satisfaction rate expressed by participants. More rigorous experimental studies are advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 45 publications
6
127
0
5
Order By: Relevance
“…Mazzoleni et al investigated whether a planned online educational program could effectively replace traditional face-to-face methods of teaching for medical staff in hospitals. They showed that electronic learning could not be a substitute for all purposes but was cost-effective for education of large populations of health-related practitioners (Mazzoleni et al, 2012 DOI:http://dx.doi.org/10.7314/APJCP.2014.15.14.5607 Teaching Breast Cancer Screening to Nurses via Text Messages in increasing knowledge and skill performance in nurses (Du et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mazzoleni et al investigated whether a planned online educational program could effectively replace traditional face-to-face methods of teaching for medical staff in hospitals. They showed that electronic learning could not be a substitute for all purposes but was cost-effective for education of large populations of health-related practitioners (Mazzoleni et al, 2012 DOI:http://dx.doi.org/10.7314/APJCP.2014.15.14.5607 Teaching Breast Cancer Screening to Nurses via Text Messages in increasing knowledge and skill performance in nurses (Du et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…13 Regarding to users motivation to pursue courses on the Proficiência Program, the data stated that 45% of them responded to have sought the course because of the content covered, 17% related to the teaching methodology, 15.9% because of the study platform, 5% tutor support and 16% listed all options. With these findings, it was observed that the content addressed satisfied the expectations of most users, so as to bring them to course completion.…”
Section: Stage 3 -Comparison: System Model Vs System Portraitmentioning
confidence: 99%
“…Students can use the smartphone to refresh their knowledge on medications and check their clinical experience in terms of hours or patient encounters in real time [5]. They can reference materials or ebooks during clinic and clinical conference to enhance debriefing and student reflection.…”
Section: Smartphone Apps For In Nursing Educationmentioning
confidence: 99%